2017
DOI: 10.1111/fme.12206
|View full text |Cite
|
Sign up to set email alerts
|

Experience counts: Integrating spearfishers’ skills and knowledge in the evaluation of biological and ecological impacts

Abstract: Fishing experience and skills are not commonly considered in recreational fishery studies. To analyse potential different biological/ecological impacts of three experience levels of spearfishers (novice, intermediate and experienced), access point surveys were conducted over a period of 10 months in São Miguel Island (Azores archipelago). Groups differed in terms of catch rate and composition, species size and vulnerability (i.e. intrinsic vulnerability index of fishes to fishing). Experienced spearfishers exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Previous studies have also observed dimensions as escape routine, relaxation or nature/outdoor enjoyment as the main reasons for taking part on the activity (e.g., Chipman & Helfrich, ; Dawson & Wilkins, ; Frijlink & Lyle, ; Ormsby, ). Knowing the main motivations that drive spearfishers to pursue the activity is an important aspect for management purposes, as it allows managers to tailor the regulations that best address both the fisheries resources conditions, and needs and expectations of all types of sub‐groups of fishers (Chipman & Helfrich, ; Diogo & Pereira, ; Diogo et al., ; Frijlink & Lyle, ; Gigliotti & Peyton, ). Note, however, that even though the questionnaire did not include economic reasons as a motivation for fishing, illegal trade of recreational catches may be an important issue in particular areas (Diogo & Pereira, ; Diogo et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also observed dimensions as escape routine, relaxation or nature/outdoor enjoyment as the main reasons for taking part on the activity (e.g., Chipman & Helfrich, ; Dawson & Wilkins, ; Frijlink & Lyle, ; Ormsby, ). Knowing the main motivations that drive spearfishers to pursue the activity is an important aspect for management purposes, as it allows managers to tailor the regulations that best address both the fisheries resources conditions, and needs and expectations of all types of sub‐groups of fishers (Chipman & Helfrich, ; Diogo & Pereira, ; Diogo et al., ; Frijlink & Lyle, ; Gigliotti & Peyton, ). Note, however, that even though the questionnaire did not include economic reasons as a motivation for fishing, illegal trade of recreational catches may be an important issue in particular areas (Diogo & Pereira, ; Diogo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the main motivations that drive spearfishers to pursue the activity is an important aspect for management purposes, as it allows managers to tailor the regulations that best address both the fisheries resources conditions, and needs and expectations of all types of sub‐groups of fishers (Chipman & Helfrich, ; Diogo & Pereira, ; Diogo et al., ; Frijlink & Lyle, ; Gigliotti & Peyton, ). Note, however, that even though the questionnaire did not include economic reasons as a motivation for fishing, illegal trade of recreational catches may be an important issue in particular areas (Diogo & Pereira, ; Diogo et al., ). The overall magnitude of the illegal recreational fishing is nonetheless unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young and inexperienced practitioners are generally very competitive in order to gain the respect and admiration of their peers (Young, Foale, & Belwood, ). In the same way, Pinheiro and Joyeux () and Diogo, Pereira, and Schmiing () verified that novice spearfishers were less selective in their fish targets. Thus, as novice spearfishers shoot with higher frequency than experienced ones, the number of contacts with corals increases.…”
Section: Discussionmentioning
confidence: 66%
“…Spearfishing constitutes an 73 active fishing mode sharing similarities to hunting because spearfishers are able to visually 74 target and select their prey (Dalzell, 1996). The size-selectivity of spearfishing depends on the 75 hunting technique (shelter seeking, ambush, sit-and-wait or direct approach) and is related to the 76 fisher's experience (Diogo et al, 2017). Similar to trophy hunting (e.g.…”
Section: Introduction 44mentioning
confidence: 99%